Penguatan Prestasi OSN Matematika SMP dan SMA melalui Kolaborasi Guru dan Siswa: Studi pada SMA Sumber Putih Kabupaten Malang - Solimun, Solimun; Hapsari, Meilina Retno; Mudjiono, Mudjiono; Lusiana, Evellin Dewi; Hidayat, Kamelia; Sianipar, Celia; Zahra, Septi Nafisa Ulluya (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
This community service program was designed to enhance the achievement of the National Science Olympiad in Mathematics through collaboration between teachers and students in Malang Regency. The background of this program lies in the limited availability of structured coaching, insufficient intensive mentoring by teachers, and the lack of competition simulations that hinder students’ academic readiness and mental resilience. The objective was to strengthen teacher competence and prepare students more effectively for the demands of Olympiad-level competitions. The program was implemented through seminars for teachers, intensive classes for students, collaborative discussion forums, competition simulations, and continuous evaluation using statistical-based monitoring. The results showed that teachers developed stronger skills in designing innovative and systematic coaching strategies, while students demonstrated improved readiness in facing challenging problems and competition pressure. The program also fostered a collaborative and participatory learning ecosystem that supports sustainable academic development. In conclusion, this initiative contributed to improving the quality of mathematics education in Malang Regency and provided a replicable model for Olympiad coaching in other schools and regions.